"The cut and thrust of industrial relations" – bullying by another name?. Issue 1 (5th March 2018) - Drake, Pat
Abstract : Purpose: The purpose of this paper is to offer a feminography, that is a "narration of a female self in a feminist age" (Abrams, 2017 ) by presenting a conceptual analysis, derived from experience, of email providing a form of discourse – that the author calls finger-speak – through which unexamined gender positioning caricatures a person's identity. In so doing, the paper provides an illustrative case of a female manager being positioned through email to "know her place, perform it and feel it" (Hey, 2011 ). Design/methodology/approach: An analysis of email foregrounds "finger-speak" as a form of digital conversation and through which people in universities may be positioned publicly but without their consent in relation to unexamined norms and assumptions. For women, it is argued, these norms are ageist and sexist. In this paper, fragments of finger-speak are collated to provide a reading of how mixing gendered norms with apparent differences of opinion constructs, via unexamined sexism, a public identity and then undermines it. Findings: Through the case presented, the author argues that, because of a shared but unarticulated shadow over women as leaders, email lays the ground for subsequent scapegoating in such a manner that the woman takes responsibility for structural challenges that rightly belong to the organisation. Originality/value: The contribution that email makes to constructing female identity in public is new, complementing other work that publicly characterises women leaders, through film (Ezzedeen, 2015 ), and through published writing such as autobiography (Kapasi et al., 2016 ). Emotional work undertaken by women in university leadership is so far under-represented in public, and email is a site through which this work becomes visible.